Factor XII blockade inhibits aortic dilatation in angiotensin II-infused apolipoprotein E-deficient mice. Issue 9 (4th May 2020) - Moran, Corey S.; Seto, Sai-Wang; Biros, Erik; Krishna, Smriti M.; Morton, Susan K.; Kleinschnitz, Christoph; Panousis, Con; Golledge, Jonathan
Abstract: Abdominal aortic aneurysm (AAA) is an important cause of mortality in older adults. Chronic inflammation and excessive matrix remodelling are considered important in AAA pathogenesis. Kinins are bioactive peptides important in regulating inflammation. Stimulation of the kinin B2 receptor has been previously reported to promote AAA development and rupture in a mouse model. The endogenous B2 receptor agonist, bradykinin, is generated from the kallikrein–kinin system following activation of plasma kallikrein by Factor XII (FXII). In the current study whole-body FXII deletion, or neutralisation of activated FXII (FXIIa), inhibited expansion of the suprarenal aorta (SRA) of apolipoprotein E-deficient mice in response to angiotensin II (AngII) infusion. FXII deficiency or FXIIa neutralisation led to decreased aortic tumor necrosis factor-α-converting enzyme (TACE/a disintegrin and metalloproteinase-17 (aka tumor necrosis factor-α-converting enzyme) (ADAM-17)) activity, plasma kallikrein concentration, and epithelial growth factor receptor (EGFR) phosphorylation compared with controls. FXII deficiency or neutralisation also reduced Akt1 and Erk1/2 phosphorylation and decreased expression and levels of active matrix metalloproteinase (Mmp)-2 and Mmp-9. The findings suggest that FXII, kallikrein, ADAM-17, and EGFR are important molecular mediators by which AngII induces aneurysm in apolipoprotein E-deficient mice. This could be a novel pathway to target in the design of drugs to limit AAA progression.